COMPUTER STORES INVENTORY SYSTEM DESIGN USING VISUAL BASIC 6.0 XYZ - Toni Anggono; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Progress in the field of computer at the time the community has been very rapid. Benefits of computerization are not only enjoyed by large companies but also by the Computer Shop and even individuals. One progress computer is a database processing system. Computerized data processing is very helpful Computer Stores in processing data, especially data items is quite high. Computerization is part of the activities of large Computer Stores Computer Stores usefulness in progress. Computerization will also show the  performance of the shop to customers that will create the impression frofesional Shop by customers. Performance of the Computer Store can not be separated from data and information quickly and accurately. Search and exchange of information in the Computer Store will be rapidly and will certainly reduce the waste of working time in the Computer Shop.